TEXTUAL AND CONTEXTUAL TERM MU’ÂSYARAH BIL MA’RUF IN THE AL-QUR'AN (LINGUISTIC STUDY) - Moh Aman; Husnul Amin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Language has many sides to life, starting from habits, customs, culture and history, so that languagestudies can provide a comprehensive understanding. As the content of the al-Qur'an is hidden in texts that canbe functioned optimally through interpretation so that it can be transformed contextually as a form ofdevelopment after understanding various textual meanings. Therefore, this research aims to find the textual andcontextual meaning of the term mu'âsyarah bil ma'ruf so that it can become an example for human life inbuilding relationships optimally. The method used in this research is a qualitative method using library datasources through a descriptive analysis process. The results of this research found that textually mu'asyarah bilma'ruf can be interpreted as proper interaction within the family which emphasizes the role played by mentowards women because women's rights are neglected. So that the meaning can be transformed contextually,that mu'asyarah bil ma'ruf is mutuality in proper interaction which emphasizes the role carried out by mentowards women and vice versa by women towards men in order to preserve life in social interactions that upholdjust human values.